The Effect of Service Quality on Duafa Patient Satisfaction at Grha Sehat Baitul Maal Muamalat Rufaida Yogyakarta - Putra, Hodiri Adi; Sundoro, Totok; Purnomo, Parmadi Sigit; Setyowati, Rustiana; Suharyanta, Dwi; Ispandiyah, Woro (COVID-19 : Journal of Health, Medical Records and Pharmacy, 2024)
Service quality assessment can be measured using five dimensions, namely assurance, reliability, responsiveness, empathy, and tangible.Grha Sehat Baitul Maal Muamalat Rufaida Yogyakarta in 17 duafa patients with the interview method there were 9 duafa patients who were dissatisfied with the service, namely in terms of physical appearance of Grha Sehat, equipment and safety guarantees for duafa patients. To determine the effect of service quality (Assurance, Reliability, Responsiveness, Empathy, Tangible) with patient satisfaction at Grha Sehat Baitul Maal Muamalat Rufaida Yogyakarta. This type of research uses quantitative research with sampling techniques, namely axial sampling. With a population of 103 patients, sample calculations using the slovin formula obtained 51 patients. The analysis used are: univariate analysis, bivariate analysis using t test and multivariate analysis using F test. Based on the results of the research conducted, there is an influence between assurance and patient satisfaction characterized by T test results of 0.001 < 0.05. There is no influence between reliability and patient satisfaction marked by T test results of 0.0687 > 0.05. There is an influence between Responsiveness characterized by T test results of 0.026 < 0.05. There is an influence between Empathy characterized by T test results of 0.025 < 0.05. There is no effect between Tangible marked with test results T 0.055 > 0.05. There is an influence on service quality (reliability, responsiveness, assurance, empathy and tangible) marked by a significant value of F test results, namely 0.000 < 0.05. Simultaneous testing with F test can be concluded that there is an influence of Service Quality on Patient Satisfaction duafa at Grha Sehat Baitul Maal Muamalat Rufaida Yogyakarta.